TINJAUAN AYAT-AYAT AL-QUR’AN TENTANG PENCIPTAAN DAN KEISTIMEWAAN ANAK BERKEBUTUHAN KHUSUS: STUDI KASUS PADA ANAK DOWN SYNDROME - Vemmy Ellengie; Moh Restu Hoeruman; Muhammad Shaleh Assingkily (Yayasan Zia Salsabila, 2025)
Children with Down Syndrome are part of a special needs group that requires integrated medical, social, and spiritual attention. From the Islamic perspective, they are not a disgrace but rather unique creations of Allah, full of wisdom and purpose. This study aims to examine Qur’anic verses related to the process of human creation and the uniqueness of children with special needs particularly those with Down Syndrome and to explore Qur’anic values that can serve as preventive, educational, and social foundations in responding to this condition. This research employs a descriptive qualitative approach using library research and thematic (maudhu‘i) interpretation methods. Primary data are derived from Qur’anic verses such as Surah Al-Mu’minun [23]: 12–14, Al-Insan [76]: 2, At-Thariq [86]: 6–7, and ‘Abasa [80]: 1–10, analyzed through classical and contemporary tafsir literature. Secondary data come from scientific literature discussing Down Syndrome from medical and social perspectives. Thematic analysis is applied to integrate the understanding of Qur’anic texts with the real-life conditions of children with Down Syndrome in society. The findings reveal that the Qur’an views the process of human creation as meaningful and purposeful, including for children born with special conditions. It also offers moral and educational foundations for supporting, accepting, and empowering children with Down Syndrome so they may live with dignity, grow optimally, and participate fairly in society. Therefore, an integrative approach that bridges divine values and medical science is essential in building an inclusive and just community.